Controle de conversores CA-CC de estágio único com cargas simultâneas - Bezerra, Luiz Daniel Santos (2018)
The thesis deals with the study of single-phase, single-phase and three-phase AC-DC converters feeding two simultaneous loads connected at the output, one being a resistive and one battery bank. When a converter feeds a pure resistive load or a non-linear load only, the control system monitors the input current to perform the power factor correction and the output voltage. In the proposed AC-DC converters with simultaneous loads, in addition to the latter quantities, a feedback loop of the current through the battery is also included, since during the recharging process it is essential that the current does not exceed the value recommenced by the battery manufacturer, thus preserving its useful life. For this purpose, a control strategy was shown based on block diagrams showing plant-FT transfer functions. The mathematical modeling of the converters under study is developed to find the transfer functions of the plant, which includes the battery model. All transfer functions were checked using the features of the PSIM program. The modified resonant controllers (CR) were used because they better adapt to the system dynamics in closed loop. It is important to emphasize that the inverters under study present applications in uninterruptible power systems (UPS) and electric vehicles (EVs). To show the feasibility of the proposal, experimental results were obtained and published for a three-phase rectifier initially of 300W and later of 3kW, also including results for a single-phase 1kW version. To simulate the designation, the converters under study are called Single Stage Converters with Simultaneous Loads (SCSL).